Microbial fuel cell biosensor for rapid assessment of assimilable organic carbon under marine conditions - Quek, J.; Cheng, Liang; Cord-Ruwisch, R. (IWA Publishing, 2015)
The development of an assimilable organic carbon (AOC) detecting marine microbial fuel cell (MFC) biosensor inoculated with microorganisms from marine sediment was successful within 36 days. This established marine MFC was tested as an AOC biosensor and reproducible microbiologically produced electrical signals in response to defined acetate concentration were achieved. The dependency of the biosensor sensitivity on the potential of the electron-accepting electrode (anode) was investigated. A linear correlation (R2 > 0.98) between electrochemical signals (change in anodic potential and peak current) and acetate concentration ranging from 0 to 150 μM (0–3600 μg/L of AOC) was achieved. However, the present biosensor indicated a different–linear relation at somewhat elevated acetate concentration ranging from 150 to 450 μM (3600–10,800 μg/L of AOC). This high concentration of acetate addition could be measured by coulombic measurement (cumulative charges) with a linear correlation. For the acetate concentration detected in this study, the sensor recovery time could be controlled within 100 min.